Effect of Self-Care Education Designed Based on Bandura's Self-efficacy Model on Patients with Hypertension: A Randomized Clinical Trial - Fatemeh Farazian; Zahra Emami Moghadam; Fatemeh Heshmati Nabavi; Hamidreza Behnam Vashani (Mashhad University of Medical Sciences, 2019)
Background: Self-care in patients with hypertension can be improved through education and implementation of learning theories. Aim: The present study aimed to determine the effect of educating self-care in patients with hypertension through the implementation of Bandura's self-efficacy model. Method: A randomized controlled clinical trial was conducted on 60 patients with hypertension who visited a randomly selected group of health centers in Mashhad, Iran, during 2017. The intervention group participated in a self-efficacy training program designed based on the self-efficacy theory in the form of four 45-minute weekly sessions. The control group received the routine treatment provided by community health centers. Self-care was measured with the questionnaire of self-care in patients with hypertension at three stages of before the intervention, immediately after the intervention, and one month later. Data were analyzed in SPSS (version 16) software using repeated measures ANOVA. Results: The mean ages were reported at 62.0±6.9 and 59.3±9.2 in the intervention and control groups, respectively. The repeated measures ANOVA showed significant differences between the two groups after the intervention in terms of adherence to medication regimen (P=0.004), engagement in physical activity (P=0.002), adherence to weight management goals (P=0.006). Significant differences were observed between the two groups in terms of their total self-care score immediately after the intervention and one month later (P=0.002). Implications for Practice: The use of Bandura's self-efficacy theory can improve the self-care in patients with hypertension. Therefore, it is recommended to conduct further studies to examine the long-term effects of training programs based on this theory on the self-care behaviors of patients with hypertension.